Integrated Analysis Of The Government Policies Along With The Implementation Frameworks For Healthcare Information System (Journal of Namibian Studies : History Politics Culture, 2023)
HealthCare information Technology (HIT) refers to a broad assortment of electronic tools that make data organization and sharing more efficient in the healthcare industry. The utilization of HIT may establish a healthcare environment that is both integrated and seamless, through the use of Electronic Health Records and telemedicine platforms. The research aims to explore the relationship between policies and implementation frameworks in determining HIT usage.We discuss HIT implementation frameworks like Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and the Technology-Organization-Environment (TOE) to understand the processes and benchmarks used to deliver a successful project. These include understanding elements related to staff expectation, applications, efficiency, social influence, patient engagement, management support, training and other facilitating conditions. The analysis helped understand the too  ls required for a successful implementation of HIT from a management perspective.The major principles of implementation frameworks was further extended to analyze the mechanism/policies followed by the United Nations and governments of Ethiopia, Bhutan and Middle eastern countries. The management of medical records has become subject to strict regulations such as the General Data Protection Regulation and the Health Insurance Portability and Accountability Act (HIPAA). These policies aimed at ensuring data security, patient privacy, compatibility, capacity building, etc.A key factor in reducing resistance to adoption is the ease of use, both in actuality and perception. The UTAUT model goes beyond TAM by placing importance on additional factors, such as the influence of peers and enabling environmental factors. WHO Europe's efforts have enabled a more comprehensive view of HIS implementation. Priorities such as digitizing health data, fostering interoperability, and strengthening institutional capacities have been agreed upon by the global community.